2015
DOI: 10.3389/fgene.2015.00241
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of GWAS candidate susceptibility loci for uterine leiomyoma in the multi-ethnic NIEHS uterine fibroid study

Abstract: We evaluated the association of 56 candidate SNPs identified in two published genome-wide association studies (GWAS) of uterine leiomyoma (UL), or fibroids, with the risk and tumor size in the multi-ethnic uterine fibroid study (NIEHS-UFS). The selected SNPs were genotyped in 916 premenopausal women of African American (AA) and European American (EA) descents and their association with the outcomes was evaluated in race-stratified models and in meta-analysis of risk in NIEHS-UFS and discovery and replication G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 44 publications
(72 reference statements)
0
10
1
1
Order By: Relevance
“…The observation of an association between rs4247357 and UL risk among women with ≥40% European ancestry supports findings from the recent 2012 GWAS among women of European descent (8). Our results do not agree with those from a smaller ultrasound screening study of European and African American women (9). The average percent European ancestry among African American women is about 20%.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The observation of an association between rs4247357 and UL risk among women with ≥40% European ancestry supports findings from the recent 2012 GWAS among women of European descent (8). Our results do not agree with those from a smaller ultrasound screening study of European and African American women (9). The average percent European ancestry among African American women is about 20%.…”
Section: Discussioncontrasting
confidence: 99%
“…It is unknown whether any of these SNPs are causally associated with UL or whether they are in LD with the causal variant. The National Institute of Environmental Health Sciences Uterine Fibroid Study (6), which analyzed 574 African American and 394 non-Hispanic European American women aged 35–51 with DNA, did not replicate FASN findings in either ethnic group (9) but power was low to detect an association.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide linkage and follow-up association studies in a meta-analysis of EA women implicated an additional locus for risk of fibroid diagnosis (Eggert et al 2012 ). The loci implicated in these previous studies ( SLK , BET1 , TNRC6B , and FASN/CCDC57 ) have been replicated among EAs (Aissani et al 2015a ; Edwards et al 2013b ), which have been evaluated but failed to replicate in AAs (Aissani et al 2015b ; Wise et al 2012 ). The predominant studies conducted among AA subjects have involved admixture mapping, which has shown significant regions of increased African ancestry in cases, particularly at 1q42.2 (Zhang et al 2015 ), 4p16, and 10q26 (Wise et al 2012 ).…”
Section: Introductionmentioning
confidence: 95%
“…Genome‐wide analyses such as exome sequencing may elucidate an additional candidate gene(s) possibly contributing to tumorigenesis. Although, the molecular mechanism of tumorigenesis in ovarian leiomyoma remains unknown, Aissani et al provided independent evidence for association of SNP of TNRC6B with both the risk and the size of uterine leiomyoma [Aissani et al, ]. However, TNRC6B resides on 22q13.1, a location different from that of PTCH1 .…”
Section: Discussionmentioning
confidence: 99%